2017
DOI: 10.1002/jum.14330
|View full text |Cite
|
Sign up to set email alerts
|

Miniprobe Endoscopic Sonography for Gastrointestinal Tract Assessment: A Case Series of 1451 Procedures

Abstract: Ram on Abad Belando, MBBS, Elena S anchez-Vizca ıno Mengual, MScConventional endoscopic sonography has allowed precise diagnostics without disturbances, and miniprobes can be easily introduced through the biopsy channel of the endoscope. Miniprobe endoscopic sonography has many benefits compared with conventional endoscopic sonography. Although there are well-known indications for miniprobe endoscopic sonography in endoscopic digestive tract assessment, there is still a need for this method to be widely spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Along with maneuverability, the diagnostic accuracy of miniprobe EUS has also been proven to be superior to conventional EUS for specific parts of the gastrointestinal tract and the pancreaticobiliary system [44]. The literature has proven that the evaluation of a few gastrointestinal pathologies with miniprobe EUS has provided additional key information, which eventually led to changes in treatment plans [45][46][47][48]. A study by Kanemaki et al on 26 patients who underwent 3D intraductal ultrasound using miniprobe EUS demonstrated that it was highly effective for accurate assessment of tumor extension, staging, and the relationship with surrounding structures [49].…”
Section: Miniature Probe Endoscopic Ultrasoundmentioning
confidence: 99%
“…Along with maneuverability, the diagnostic accuracy of miniprobe EUS has also been proven to be superior to conventional EUS for specific parts of the gastrointestinal tract and the pancreaticobiliary system [44]. The literature has proven that the evaluation of a few gastrointestinal pathologies with miniprobe EUS has provided additional key information, which eventually led to changes in treatment plans [45][46][47][48]. A study by Kanemaki et al on 26 patients who underwent 3D intraductal ultrasound using miniprobe EUS demonstrated that it was highly effective for accurate assessment of tumor extension, staging, and the relationship with surrounding structures [49].…”
Section: Miniature Probe Endoscopic Ultrasoundmentioning
confidence: 99%
“…EUS can alternatively be performed with an ancillary miniprobe (EUS-MP) that passes through the biopsy channel of a standard endoscope or colonoscope, as utilized in the pediatric EoE study 27 . Thus, EUS-MP could have wider applications, reaching areas of the gastrointestinal tract that are only accessible to a narrower scope 57 and potentially being available during any endoscopic procedure. Miniprobes are available with 12 or 20 MHz frequency.…”
Section: Different Endosonography Instruments and Techniquesmentioning
confidence: 99%
“…On conventional ultrasound images, blood flow characteristics cannot be readily assessed so vessels appear black. Contrast enhance EUS uses gas-filled microbubbles injected intravenously during the EUS exam after baseline images have been obtained 57,62 . CEU images are obtained from the arterial (10 to 20 seconds after injection) to the venous phases (30-45 seconds after injection).…”
Section: Future Frontiers Of Endoscopic Point Of Care Ultrasoundmentioning
confidence: 99%
“…Additionally, mEUS can provide precise indications by imaging the extrinsic compression, the size of intramural tumours, internal properties, originating wall layer, and the associated echostructure of the colorectal tracts. 9 However, the clinical role of mEUS in differentiating various colorectal submucosal lesions and its adjuvant role in clinical treatment decisions are barely explored. There is scant data on certain aspects of the mEUS differentiating diagnosis and the management of colorectal submucosal lesions.…”
Section: Introductionmentioning
confidence: 99%
“…There is scant data on certain aspects of the mEUS differentiating diagnosis and the management of colorectal submucosal lesions. Previous studies of mEUS only explored the applications of mEUS on a single tumour/submucosal lesion, and there is no systematic evidence on the comparison of the effects of mEUS across different submucosal lesions 2,[6][7][8][9][10][11][12][13][14][15][16] The current study was planned to evaluate the efficacy of mEUS for the diagnosis and adjuvant treatment of patients with colorectal submucosal lesions.…”
Section: Introductionmentioning
confidence: 99%